Don't Look Now. - Gildersleeve, Jessica (Devil's advocates., 2017)
Nicolas Roeg's Don't Look Now (1973) has been called "a ghost story for adults." Certainly, in contrast to the more explicitly violent and bloodthirsty horror films of the 1970s, Don't Look Now seems of an entirely different order. Yet this supernaturally inflected tale of a child's accidental drowning, and her parents' desperate simultaneous recoil from her death and pursuit of her ghost, Don't Look Now is horrific at every turn. This book argues for it as a particular kind of horror film, one which depends utterly on the narrative of trauma'on the horror of unknowing, of seeing too late, and of the failures of paternal authority and responsibility. Jessica Gildersleeve positions Don't Look Now within a discourse of midcentury anxiety narratives primarily existing in literary texts. In this context, it represents a cross over or a hinge between literature and film of the 1970s, and the ways in which the women's ghost story or uncanny story turns the horror film into a cultural commentary on the failures of the modern family.